Association between Cluster of Lifestyle Behaviors and HOMA-IR among Adolescents: ABCD Growth Study - Werneck, André Oliveira [UNESP]; Agostinete, Ricardo Ribeiro [UNESP]; Cayres, Suziane Ungari [UNESP]; Urban, Jacqueline Bexiga [UNESP]; Wigna, Andréa [UNESP]; Chagas, Lucas Gabriel de Moraes [UNESP]; Torres, Wesley [UNESP]; Fernandes, Rômulo Araújo [UNESP] (MDPI, 2018)
Objective: To analyze the association of potential risk factors to health with body fatness and insulin resistance. Baseline measures of the ongoing longitudinal Analysis of Behaviors of Children During (ABCD) Growth Study. Materials and Methods: The sample was composed of 280 adolescents of both sexes (198 boys and 82 girls) aged from 10 to 18 years. Four risk factors were considered, as follows: no sports practice, skipping breakfast, poor sleep quality, and TV viewing. The outcomes considered were insulin resistance (HOMA-IR) and body fatness (densitometer scanner). Age, sex, maturity offset, and ethnicity were treated as covariates. Results: No sports practice and skipping breakfast were associated with higher body fatness (Sports practice: Wald: 8.786; p = 0.003. Breakfast: Wald: 9.364; p = 0.002). Poor sleep quality was related to a greater HOMA-IR index (Wald: 6.013; p = 0.014). Adolescents with ≥3 risk factors presented a higher risk of high HOMA-IR (OR = 4.89 (95%CI: 1.61 to 14.84)) than their counterparts with no risk factors. Conclusion: Lifestyle risk factors seem relevant to affect obesity and insulin resistance, while the aggregation of these risk factors affects insulin resistance, independent of adiposity.
Keywords: adiposity; health risk behaviors; insulin resistance; youth